2016
DOI: 10.1155/2016/1089196
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Increased Daytime Sleepiness in Patients with Chronic Obstructive Pulmonary Disease: A Cross-Sectional Study

Abstract: Background. Patients with Chronic Obstructive Pulmonary Disease (COPD) suffer from increased daytime sleepiness. The aim of this study was to identify potential predictors of subjective daytime sleepiness with special regard to sleep-related breathing disorder and nocturnal activity. Methods. COPD patients were recruited at the University Hospital Basel, Switzerland. COPD risk groups A–D were determined according to spirometry and COPD Assessment Test (CAT). Breathing disorder evaluation was performed with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Our results did not show advancing age, medical conditions other than arthritis, or cognitive impairment as having statistically significant associations with the ESS. With respect to the effect of age, results from CHS also showed no association between age and higher scores, while other studies found lower ESS scores in older as compared to middle‐aged persons . We again posit that a higher tolerance for hypersomnia, the paradox of well‐being, or reduced awareness of symptom severity may explain the lack of association of age with patient‐reported hypersomnia.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Our results did not show advancing age, medical conditions other than arthritis, or cognitive impairment as having statistically significant associations with the ESS. With respect to the effect of age, results from CHS also showed no association between age and higher scores, while other studies found lower ESS scores in older as compared to middle‐aged persons . We again posit that a higher tolerance for hypersomnia, the paradox of well‐being, or reduced awareness of symptom severity may explain the lack of association of age with patient‐reported hypersomnia.…”
Section: Discussioncontrasting
confidence: 48%
“…With respect to the effect of age, results from CHS also showed no association between age and higher scores, while other studies found lower ESS scores in older as compared to middleaged persons. 7,43,44 We again posit that a higher tolerance for hypersomnia, the paradox of well-being, or reduced awareness of symptom severity may explain the lack of association of age with patient-reported hypersomnia. Additionally, the adverse effect of aging on sleep architecture occurs predominantly in middle age.…”
Section: Discussionmentioning
confidence: 90%
“…Linked to lack of energy is also feeling drowsy, and in the present study, the probability of occurrence of feeling drowsy was high in all three classes at 12 months compared to baseline [13]. Drowsiness, or daytime sleepiness, may be caused by nocturnal respiratory disturbances in patients with more severe COPD symptoms [46] and is reported as a common symptom in COPD [47,48]. Difficulty sleeping was rated considerably lower, which may suggest that the symptom of drowsiness may occur due to the total burden and the high number of symptoms.…”
Section: Discussionmentioning
confidence: 75%
“…Studies have verified that, as the disease is chronic, COPD patients have a susceptibility to daytime somnolence [31]. Thus, the more severe the COPD, the greater the daytime somnolence [32].…”
Section: Discussionmentioning
confidence: 97%